2004
DOI: 10.1111/j.0013-9580.2004.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Treatment of Refractory Status Epilepticus: A Study of 31 Episodes

Abstract: Summary:Purpose: Refractory status epilepticus (RSE) is a critical medical condition with high mortality. Although propofol (PRO) is considered an alternative treatment to barbiturates for the management of RSE, only limited data are available. The aim of this study was to assess PRO effectiveness in patients with RSE.Methods: We retrospectively considered all consecutive patients with RSE admitted to the medical intensive care unit (ICU) between 1997 and 2002 treated with PRO for induction of EEGmonitored bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
2
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 65 publications
(90 reference statements)
3
105
2
9
Order By: Relevance
“…Propofol at subanesthetic concentrations exhibits anticonvulsant properties in refractory status epilepticus patients (Brown and Levin, 1998;Prasad et al, 2001;Rossetti et al, 2004). However, several studies have cautioned against the use of propofol as an anticonvulsant because of serious side effects (Claassen et al, 2002;Marik, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Propofol at subanesthetic concentrations exhibits anticonvulsant properties in refractory status epilepticus patients (Brown and Levin, 1998;Prasad et al, 2001;Rossetti et al, 2004). However, several studies have cautioned against the use of propofol as an anticonvulsant because of serious side effects (Claassen et al, 2002;Marik, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…general anesthetic; however, at subanesthetic doses, propofol is used clinically during refractory status epilepticus, a critical medical emergency with mortality rates as high as 76% in elderly patients (Prasad et al, 2001;Claassen et al, 2002;Marik and Varon, 2004;Rossetti et al, 2004). Propofol has been shown to inhibit sodium currents in mammalian cell lines expressing rat Na v 1.2 (Rehberg and Duch, 1999), to activate GABA currents in hippocampal neurons (Orser et al, 1994), and to inhibit L-type calcium currents in cortical neurons (Martella et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Despite the claims of proconvulsant activity of propofol, there is also evidence of its anticonvulsant action. [3][4][5] Severe neuroexcitatory symptoms are rare side effect of propofol which can occur during the induction, maintenance or emergence from anesthesia. 6 We present one such case of severe neuroexcitatory symptoms after induction with propofol which was managed with injection thiopentone and midazolam.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study of 33 children with refractory status epilepticus indicated that propofol was more effective than thiopental in terminating seizures [15] and studies in adults indicated that propofol terminated seizures in 67% of patients [16]. With this information in mind, we therefore aimed at investigating the effects of propofol on epileptiform activity and hippocampal morphology in rat models of seizure induced by hyperthermia and/or pilocarpine induced Status Epilepticus (SE), alone or in combination.…”
Section: Introductionmentioning
confidence: 99%